THE USE OF WORD MAPPING TECHNIQUE IN TEACHING VOCABULARY - Haras L.M, Hediza; Sutapa, Y. Gatot; Susilowati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of this research was to find out the effectiveness of the use of Word Mapping technique in teaching vocabulary. To achieve the objectives of the research, a pre experimental research was conducted at SMP Negeri 14 Pontianak with the subject of the research was the eighth grade students in class VIIIA in academic year 2015/2016 which was chosen by using cluster random sampling technique. The findings of the research obviously showed that there was a significant difference of the students’ achievement before and after Word Mapping technique was applied, and that the use of the technique had a highly significant effect on the students’ vocabulary mastery shown by the students’ improved scores on the posttest. To sum up, the present research findings proved that the use of Word Mapping technique is highly effective in teaching vocabulary to the eighth grade students of SMP Negeri 14 Pontianak academic year 2015/2016. Keywords: Word Mapping Technique, Vocabulary Mastery, Vocabulary Teaching Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan teknik Word Mapping pada pengajaran kosa kata. Untuk mencapai tujuan penelitian, sebuah penelitian pre-experimental telah dilakukan di SMP Negeri 14 Pontianak dengan subjek penelitian adalah siswa kelas VIII A pada tahun ajaran 2015/2016 yang telah dipilih menggunakan teknik cluster random sampling. Hasil penelitian dengan jelas menunjukkan bahwa terdapat perbedaan yang signifikan terhadap prestasi siswa sebelum dan sesudah teknik Word Mapping diterapkan, dan penggunaan teknik teresebut mempunyai efek yang signifikan terhadap penguasaan kosa kata siswa yang ditunjukkan dari peningkatan skor posttest siswa. Dapat disimpulkan bahwa, penggunaan teknik Word Mapping efektif terhadap pengajaran kosa kata pada siswa kelas VIII A di SMP Negeri 14 Pontianak tahun ajaran 2015/2016. Kata kunci: Teknik Word Mapping, Penguasaan Kosa Kata, Pengajaran Kosa Kata